Polycystic Ovary Syndrome: Prevalence and impact on the quality of life in university students (Research, Society and Development, 2024)
Polycystic ovary syndrome is a very common clinical condition in gynecological and endocrinological practice, affecting 6 to 16% of women of reproductive age. The main clinical manifestations of this syndrome include the presence of hyperandrogenism, oligo-amenorrhea, and chronic anovulation. As a result of these manifestations, many women experience hirsutism, obesity, and may develop infertility, and these factors are directly related to the self-esteem and quality of life of individuals with polycystic ovary syndrome. Thus, the present study aimed to observe which manifestations are more prevalent and how they impact the quality of life of the observed group of female students. The research was conducted individually with 100 female students, over 18 years of age, who have polycystic ovary syndrome, enrolled in the 1st to 6th year of the medical course at the Faculdade de Medicina de Itajubá and the Universidade do Vale do Sapucaí, through a pre-formulated questionnaire sent via the "Google Forms" tool. The results obtained confirmed the initial hypothesis of the study, as the majority of participants reported that symptoms such as hirsutism, excess weight, menstrual disturbances, and fear of infertility directly affect their quality of life and self-esteem, leading to emotional symptoms and psychological disorders. The objective of the study was to observe the signs and symptoms of polycystic ovary syndrome and how they impact the quality of life of the participants. Therefore, this analysis is important so that new interventions can be suggested and implemented, improving treatment and ensuring a better quality of life for patients.